COVID-19 influenced gut dysbiosis, post-acute sequelae, immune regulation, and therapeutic regimens - Raj, Sterlin T.; Bruce, Alexander W.; Anbalagan, Muralidharan; Srinivasan, Hemalatha; Chinnappan, Sasikala; Rajagopal, Mogana; Khanna, Kushagra; Chandramoorthy, Harish C.; Mani, Ravishankar Ram (Frontiers in Cellular and Infection Microbiology, 2024)
The novel coronavirus disease 2019 (COVID-19) pandemic outbreak caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has garnered unprecedented global attention. It caused over 2.47 million deaths through various syndromes such as acute respiratory distress, hypercoagulability, and multiple organ failure. The viral invasion proceeds through the ACE2 receptor, expressed in multiple cell types, and in some patients caused serious damage to tissues, organs, immune cells, and the microbes that colonize the gastrointestinal tract (GIT). Some patients who survived the SARS-CoV-2 infection have developed months of persistent long-COVID-19 symptoms or post-acute sequelae of COVID-19 (PASC). Diagnosis of these patients has revealed multiple biological effects, none of which are mutually exclusive. However, the severity of COVID-19 also depends on numerous comorbidities such as obesity, age, diabetes, and hypertension and care must be taken with respect to other multiple morbidities, such as host immunity. Gut microbiota in relation to SARS-CoV-2 immunopathology is considered to evolve COVID-19 progression via mechanisms of biochemical metabolism, exacerbation of inflammation, intestinal mucosal secretion, cytokine storm, and immunity regulation. Therefore, modulation of gut microbiome equilibrium through food supplements and probiotics remains a hot topic of current research and debate. In this review, we discuss the biological complications of the physio-pathological effects of COVID-19 infection, GIT immune response, and therapeutic pharmacological strategies. We also summarize the therapeutic targets of probiotics, their limitations, and the efficacy of preclinical and clinical drugs to effectively inhibit the spread of SARS-CoV-2.